Residents Social Behavior in The Implementation of Denpasar City Waste Management Policy - Emmanuel Chinedu Elele; I Nyoman Subanda (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
With the increasing level of waste generation in Denpasar city reaching above 1000 tons per day in the midst of rapid population growth and a surge in tourism activities, residents’ adherence to    waste management procedures constitutes a vital component in the government policy strategy towards tackling waste management challenges related  to health ,  hygiene and environmental sustainability. This study aims to ascertain and analyze, implementation of Denpasar City waste management policy, to ascertain and analyze the social behavior of Denpasar city residents in the implementation of waste management policy, and to find out and analyze factors influencing the implementation of Denpasar city waste management policy. Data were obtained through in-depth interviews with research informants selected through purposive sampling technique, observation, and review of documents. Triangulation method was used for data validation while Miles-Huberman's interactive data analysis model was used analysis. Conclusion drawn from this research is that residents' parochial and non-compliance behavior to waste management standard operational procedures hinder effective implementation of waste management policy in Denpasar city..